A USEFUL METHODOLOGY TO SELECT LIPASE-CATALYZED TRANSESTERIFICATION AIMING BIODIESEL APPLICATION - Facchini, F. D. A.; Vici, A. C.; Pereira, M. G.; Oliveira, M. F. de; Batista, A. C. F.; Vieira, A. T.; Silva, T. A.; Jorge, J. A.; Polizeli, M. L. T. M. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The application of lipases in various fields has been notably increased in the last few decades and qualitative/quantitative improvements need to be done. However, many methodologies of screening are described in order to find a good lipase producer and statistical optimization is a necessary tool to improve lipase production. In this work, an isolation of filamentous fungi lipase producers and a transesterification capacity screening was evaluated. Four fungi were chosen to the transesterification reaction assays and the best fungus selected was submitted to a submerged fermentation. Parameters of the culture medium were optimized using response surface methodology. Selected liquid medium was SR at 30 °C, 72 h, 100 rpm. Corn oil was the best carbon source and together with Tween 80 increased two-fold the lipase activity. After the experimental design, the new medium optimized were 3.5-fold higher than the original liquid medium and was composed by 0.5% corn oil, 0.012% MgSO4.7H2O, 0.015% KH2PO4, 0.05% NH4H2PO4. Hence, the lipase produced proved its transesterification capacity and can be used for biodiesel production.